Identification and Analysis of Anticancer Therapeutic Targets from the Polysaccharide Krestin (PSK) and Polysaccharopeptide (PSP) Using Inverse Docking - Carlos Iván López-Gil; Alejandro Téllez-Jurado; Marco Antonio Velasco-Velázquez; Miguel Angel Anducho-Reyes (Molecules)
The natural compounds PSK and PSP have antitumor and immunostimulant properties. These pharmacological benefits have been documented in vitro and in vivo, although there is no information in silico which describes the action mechanisms at the molecular level. In this study, the inverse docking method was used to identify the interactions of PSK and PSP with two local databases: BPAT with 66 antitumor proteins, and BPSIC with 138 surfaces and intracellular proteins. This led to the identification interactions and similarities of PSK and the AB680 inhibitor in the active site of CD73. It was also found that PSK binds to CD59, interacting with the amino acids APS22 and PHE23, which coincide with the rlLYd4 internalization inhibitor. With the isoform of the K-RAS protein, PSK bonded to the TYR32 amino acid at switch 1, while with BAK it bonded to the region of the α1 helix, while PSP bonded to the activation site and the C-terminal and N-terminal ends of that helix. In Bcl-2, PSK interacted at the binding site of the Venetoclax inhibitor, showing similarities with the amino acids ASP111, VAL133, LEU137, MET115, PHE112, and TYR108, while PSP had similarities with THR132, VAL133, LEU137, GLN118, MET115, APS111, PHE112, and PHE104.